Analisis Kesehatan dan keselamatan kerja (K3) dengan metode Hazard Identification, Risk Assesment and Risk Control (HIRARC) pada unit Kiln PT. Semen Indonesia (Persero) Tbk. Pabrik Tuban - muhamad nur, firmansyah; Pratama, Rio Candra (Universitas Bojonegoro, 2022)
Occupational safety and health is a program created in an effort to prevent work accidents and occupational diseases. The goal is to create a comfortable, safe, and healthy workplace so that it can reduce the risk of work accidents as much as possible. The method used in reducing the risk of work accidents at PT. Semen Indonesia (Persero) Tbk. The Tuban factory, namely the HIRARAC (Hazard Identification, Risk Assessment, and Control) method, After conducting the research, there are several sources of danger that exist in the kiln unit, namely operating the kiln when the percentage of carbon dioxide is high, replacing burnerheads, operating belt conveyors, repairing electrical panels, checking kiln shell inlets, breaking dead-end production lines, and adding chemical mixtures. Then they carried out risk management efforts to reduce the risk of workplace accidents. Risk control measures are guided by the control hierarchy, namely by means of elimination, substitution, design, administration, and PPE. Risk control that has been carried out is by installing and complying with safety lines, barricades, safety signs, and using PPE, including safety helmets, safety shoes, hand gloves, a full body harness, safety goggles, fire-resistant clothing (nomex), and respirators.